Rules of Origin in ASEAN+1 FTAs and the Value Chain in East Asia - Erlinda M. Medalla; Maureen Ane D. Rosellon (Philippine Institute for Development Studies (PIDS), 2012)
This paper discusses the nature of the rules of origin (ROOs) in the ASEAN+1 FTAs, particularly with respect to features and characteristics that could either facilitate or hinder the development of value chains, and the participation of firms in the increased globalization of production. By examining both the types of ROOs used and the origin certification procedures employed in these FTAs, the paper arrives at recommendations for reforms that could facilitate trade and the linkages in the value chain system in the region. Case studies on automotive and electronic sectors provide further insights.
Keywords: 330; rules of origin; value chain; East Asia; ASEAN Free Trade Agreement (AFTA)